Don’t Be Afraid to Fail Because You Can Learn From It! How Intrinsic Motivation Leads to Enhanced Self-Development and Benevolent Leadership as a Boundary Condition - Zhou, Qiwei; Mao, Jih-Yu; Tang, Fangcheng (Frontiers in Psychology, 2020)
Employee learning from failures is key to effective employee functioning and long-term sustainable development. Although failure is an essential part of the learning process, it is less certain of why individuals would learn from failures and the benefits associated with it. Thus, it is significant to explore the cause and the consequence of learning from failures. Drawing upon self-determination theory, we explore the antecedent, consequence, and boundary condition of employee learning from failures. Random full-time employees in China were recruited to participate in the two-wave survey study via an online survey platform. Empirical results of 381 employees indicate that employee intrinsic motivation is positively related to employee learning from failures, which in turn facilitates employee self-development. Moreover, we found that benevolent leadership, a leadership style that is prevalent in the Chinese work context, plays an important moderating role in affecting the saliency of the indirect effect. Specifically, the indirect effect is more salient when benevolent leadership is higher. We test the hypotheses in SPSS using linear regressions and the PROCESS macro. Our study provides important implications for both theory and practice. Limitations and future research directions are also discussed.